The current standard of care and the unmet needs for axial spondyloarthritis. (16th November 2018) - Noureldin, Basil; Barkham, Nick
Abstract: The aim of this article is to explore the benefits and limitations of the established treatments for axial SpA (axSpA), including physiotherapy, NSAIDs, conventional synthetic DMARDs and biologic DMARDs such as TNF inhibitors (TNFis). It also briefly discusses the emerging role of anti-IL-17 therapy, which could be used as a valuable alternative to first-line biologic DMARD treatment or as a second-line treatment for patients who are inadequate responders to TNFi therapy, as evidenced by various studies. Exercise programmes improve health-related quality of life and hydrotherapy improves disease activity and functional parameters in AS. NSAIDs have been proven to substantially relieve symptoms in 70–80% of patients and enhance physiotherapy by reducing pain and stiffness. The role of NSAIDs in preventing radiographic progression remains unclear. The use of conventional synthetic DMARDs (csDMARDs) is limited to peripheral arthritis; there is insufficient evidence to support the use of csDMARDs for axial disease. TNFi therapy reduces the disease activity of axSpA, however, as not all patients respond to treatment in the same way, it is good to have other therapeutic options available. Finally, this article explores the potential for IL-17 inhibition in AS and introduces clinical data for secukinumab, a fully human monoclonal antibody targeting IL-17A.